Algoritmos de reconocimientos de gestión de la mano basado en tecnología Kinect" - Barros Rengifo, Nicandro Rafael (2013)
In this thesis project MathKids a system called Learning of Mathematics was conducted, using the Kinect sensor interface for recognizing hand gestures. Is designed for children and adults to survey figures, location of figures and interact more quickly and efficiently without using any command or control and to better use and management of users. For the development of the thesis project first the sensor Kinect Xbox 360 was used, as this gesture recognition was implemented and finally concluded with the creation of MathKids system through the interface Kinect sensor with recognition of gestures hand. Using the OpenNI Seller was very useful for the interpretation of the Kinect sensor signals, allowing us to interact with one man - machine. According to tests carried out, determined the creation of MathKids system through the interface Kinect sensor with recognition of hand gestures is for children to develop their psychomotor and mental skills for the future of education in Ecuador